Let us solve the differential equation "(2x+3y)dx-4(x+1)dy=0". It follows that "x=-1" is a solution. Further, we will assume that "x\\ne -1". So, in this case the equation is equivalent to the equation
"\\frac{dy}{dx}=\\frac{2x+3y}{4(x+1)}".
Let us solve the system "\\begin{cases}2x+3y=0\\\\x+1=0\\end{cases}" which is equivalent to "\\begin{cases}x=-1\\\\y=\\frac{2}{3}\\end{cases}".
Let us introduce a substitution "\\begin{cases}x=t-1\\\\y=z+\\frac{2}{3}\\end{cases}".
Then we have he differential equation "\\frac{dz}{dt}=\\frac{2(t-1)+3(z+\\frac{2}{3})}{4(t-1+1)}=\\frac{2t+3z}{4t}".
Let us introduce a substitution "z=t\\cdot u(t)". Then "dz=u\\cdot dt+t\\cdot du" and thus
"\\frac{u\\cdot dt+t\\cdot du}{dt}=\\frac{2t+3tu}{4t}= \\frac{2+3u}{4}"
"u+t\\frac{du}{dt}= \\frac{2+3u}{4}"
"t\\frac{du}{dt}= \\frac{2+3u}{4}-u=\\frac{2-u}{4}"
If "u=2", then "z=2t", "y-\\frac{2}{3}=2x+2", and therefore, "y=2x+2+\\frac{2}{3}=2x+\\frac{8}{3}". Since "(2x+3y)dx-4(x+1)dy=(2x+3(2x+\\frac{8}{3}))dx-4(x+1)2dx=(8x+8)dx-8(x+1)dx=0," we conclude that "y=2x+\\frac{8}{3}" is a solution of the differential equation.
Let "u\\ne 2". Then
"\\frac{4du}{2-u} =\\frac{dt}{t}"
"\\int\\frac{4du}{2-u} =\\int\\frac{dt}{t}"
"-4\\ln|2-u|+\\ln|C|=\\ln|t|"
"\\ln|C|=\\ln|t|+ \\ln(2-u)^4=\\ln|t(2-u)^4|"
"t(2-u)^4=C"
"t(2-\\frac{z}{t})^4=C"
"(x+1)(2-\\frac{y-\\frac{2}{3}}{x+1})^4=C"
"(x+1)(\\frac{2x-y+\\frac{8}{3}}{x+1})^4=C"
"(2x-y+\\frac{8}{3})^4=C(x+1)^3"
If "C=0", then we have the solution "y=2x+\\frac{8}{3}".
Therefore, we have the following solution of the differentail equation "(2x+3y)dx-4(x+1)dy=0":
"(2x-y+\\frac{8}{3})^4=C(x+1)^3" and "x=-1."
Comments
Leave a comment